Facile mechanochemical synthesis of nano SnO2/graphene composite from coarse metallic sn and graphite oxide: An outstanding anode material for lithium-ion batteries - Ye, F.; Zhao, B.; Ran, R.; Shao, Zongping (Wiley-VCH Verlag, 2014)
A facile method for the large-scale synthesis of SnO2 nanocrystal/graphene composites by using coarse metallic Sn particles and cheap graphite oxide (GO) as raw materials is demonstrated. This method uses simple ball milling to realize a mechanochemical reaction between Sn particles and GO. After the reaction, the initial coarse Sn particles with sizes of 3-30 µm are converted to SnO2 nanocrystals (approximately 4 nm) while GO is reduced to graphene. Composite with different grinding times (1 h 20 min, 2 h 20 min or 8 h 20 min, abbreviated to 1, 2 or 8 h below) and raw material ratios (Sn:GO, 1:2, 1:1, 2:1, w/w) are investigated by X-ray diffraction, X-ray photoelectron spectroscopy, field-emission scanning electron microscopy and transmission electron microscopy. The as-prepared SnO2/graphene composite with a grinding time of 8 h and raw material ratio of 1:1 forms micrometer-sized architected chips composed of composite sheets, and demonstrates a high tap density of 1.53 gcm-3. By using such composites as anode material for LIBs, a high specific capacity of 891 mAhg -1 is achieved even after 50 cycles at 100 mAg-1. A facile ball-milling method for large-scale synthesis of a SnO2 nanocrystal/graphene composite by using coarse metallic Sn particles and cheap graphite oxide (GO) as raw materials is demonstrated. By using the SnO 2 nanocrystals/graphene composite as an anode material for lithium-ion batteries, a high specific capacity of 891 mAhg-1 was achieved even after 50 cycles at 100 mAg-1 (see figure). © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.